ANALYSIS OF THE EFFECT OF PBL MODEL ASSISTED BY E-LKPD WIZER.ME ON CRITICAL THINKING SKILLS AND STUDENT LEARNING OUTCOMES OF HIGH SCHOOL PHYSICS - Pratiwi, Anisa Septi; Maryani, Maryani (Universitas Negeri Padang, 2024)
Learning is a process to arrange and organize an environment that can grow and encourage students to learn. The critical thinking skills and academic achievements of students in Indonesia remain at a relatively low level. This diminished level of critical thinking skills and student learning outcomes is attributed to a lack of interest among students in the learning process.Appropriate learning models and media are very important in the learning process. The utilized research methodology is a true experiment with a quantitative approach. Data analysis was carried out using normality tests and statistical tests. Based on the normality test, the critical thinking ability data is normally distributed, so the data is continued with the T Test (Independent Sample T-Test) which results in an Asymp. Sig (2-tailed) of 0.000 is less than 0.05, so there is an effect of applying the PBL model assisted by E-LKPD wizer.me on the results of students' critical thinking skills on dynamic fluid material in high school. While the normality test of learning outcomes states that the data is not normally distributed, so data analysis is carried out with the Man Whitney U Test. Based on the Man Whitney U Test, the Asymp. Sig (2-tailed) of 0.000 is less than 0.05, so it can be concluded that there is an effect of the application of PBL model assisted by E-LKPD wizer.me on student learning outcomes on dynamic fluid material in high school. The conclusion of this study is that the application of the PBL model with the support of E-LKPD wizer.me has a significant effect on critical thinking skills in high school. Apart from that, the application of the PBL model assisted by E-LKPD wizer.me also has a significant influence on high school physics learning outcomes.Keywords: PBL, E-LKPD, Wizer.we, Critical thinking, and learning outcomes